Cultivation of Chlorella sorokiniana in a bubble-column bioreactor coupled with cooking cocoon wastewater treatment: effects of initial cell density and aeration rate - Chunye Xue (IWA Publishing, 2021)
Previous studies have documented that Chlorella sorokiniana could grow well on cooking cocoon wastewater (CCW) with a maximum biomass of 0.49 g/L. In order to further enhance the biomass production and nutrient removals, a bubble-column bioreactor was designed and performed to cultivate C. sorokiniana in CCW, and two main cultivation parameters were investigated in this work. Results showed that a maximum algal biomass, specific growth rate, and biomass productivity of 2.83 g/L, 0.854 d−1, and 476.25 g/L/d, respectively, were achieved when this alga was cultivated in the bioreactor with an initial cell density of 0.8 g/L and an aeration rate of 3.34 L air/L culture/min; meanwhile, removal efficiencies of ammonium, total nitrogen, total phosphorus, and chemical oxygen demand reached 97.96, 85.66, 97.96, and 86.43%, respectively, which were significantly higher than that obtained in our previous studies. Moreover, chemical compositions in the algal cells varied with the changes of cultivation conditions (i.e., initial cell density and aeration rate). Thus, it is concluded that (1) the bubble-column bioreactor was suitable for cultivation of C. sorokiniana coupled with the CCW treatment and (2) initial cell density and aeration rate affected the biomass production, nutrient removals and chemical compositions of this alga. HIGHLIGHTS A bubble-column bioreactor was designed and performed in this work.; The bioreactor was suitable to cultivate C. sorokiniana using CCW.; Initial cell density and aeration rate were two key factors during the cultivation.; Biomass production and nutrient removal were enhanced under the optimal conditions.; Algal chemical compositions varied with the changes in cultivation conditions.;